Influenza: cause or excuse? An analysis of flu’s influence on worsening mortality trends in England and Wales, 2010-19 - Hiam, L; McKee, M; Dorling, D (Oxford University Press, 2024)
Background England and Wales experienced a stagnation of previously improving life expectancy during the 2010s. Public bodies cited influenza as an important cause. Sources of data We used data from the Office for National Statistics to examine mortality attributed directly to influenza and to all influenza-like diseases for the total population of England and Wales 2010–19. Several combinations of ICD-10 codes were used to address the possibility of under-counting influenza deaths. Areas of agreement Deaths from influenza and influenza-like diseases declined between 2010 and 2019, while earlier improvements in mortality from all causes of death were stalling and, with some causes, worsening. Our findings support existing research showing that influenza is not an important cause of the stalling of mortality rates 2010–19. Areas of controversy Influenza was accepted by many as an important cause of stalling life expectancy for much of the 2010s, while few in public office have accepted austerity as a key factor in the changes seen during that time. Growing points This adds to the mounting evidence that austerity damaged health prior to COVID-19 and left the population more vulnerable when it arrived. Areas for developing timely research Future research should explore why so many in public office were quick to attribute the change in trends in overall mortality in the UK in this period to influenza, and why many continue to do so through to 2023 and to deny the key role of austerity in harming population health.